PENDAMPINGAN STANDARISASI PRODUKSI MINYAK BUAH MERAH UNTUK MENINGKATKAN KEBERDAYAAN KELOMPOK TANI WADIO DI NABIRE, PAPUA - Dharsono, Wardhana; Telussa, Rivaldo Paul; Tokoro, Errol Lesly; Pigai, Hengki; Wakey, Williem Henok; Suryadi, Suryadi (Yayasan Education and Social Center, 2025)
Red fruit (Pandanus conoideus Lamk.) is a local commodity in Nabire, Papua, with high nutritional and economic potential, particularly through the production of red fruit oil. However, the red fruit processing practices of the Wadio farmer group were still traditional, unstandardized, and poorly documented, resulting in low and inconsistent product quality and yield. This community service program aimed to improve both the production process and the empowerment level of the farmer group in terms of production, management, marketing, and socio–organizational aspects. The program was carried out in Wadio Atas, Nabire, using a participatory empowerment approach through socialization, technical training, hands-on mentoring, and simple evaluation. Baseline conditions were identified through observation and interviews, followed by pre- and post-training assessments of knowledge, practical skills, and satisfaction. The results show an improvement in process standardization, documentation of raw materials and yields, and understanding of basic business concepts. The majority of participants moved from relying on single-step, undocumented processing to applying multi-stage, documented standard operating procedures (SOP). Simple quantitative evaluation indicated that 95–100% of participants reached good to very good categories in knowledge and skills indicators after the program, and 98% expressed satisfaction with the activities. These changes reflect an increased empowerment level of the partner group, particularly in production and basic management capabilities, providing a foundation for further development of marketing and socio-economic impact